Motivational approach to lifestyle modification intervention on cardiometabolic risk profiles among obese adults: A randomized controlled trial - Shahadan, Siti Zuhaidah; Daud, Azlina; Md Isa, Muhammad Lokman; Ibrahim, Muhammad; Draman, Samsul (2019)
This study aims to determine the effect of lifestyle modification intervention with a motivational approach (LMI-MA) on cardiometabolic risk (CMR) profiles among obese adults. This is a randomized controlled trial with an intervention group who received a 6-month LMI-MA and a control group, who received a 6-month standard LMI. The findings showed that the obese adults in the intervention group (n=40) had a positive outcome to the CMR profile through a significant reduction in the body mass index (p=0.002) and a significant rise in high-density lipoprotein level (p=0.021) after six months. The intervention group also achieved a reduction in the low-density lipoprotein (LDL) and high-sensitivity C-reactive protein (hs-CRP) level after six months. Contrariwise, the control group (n=39) had an unexpected significant rise in fasting blood glucose level (p=0.012) and the LDL and hs-CRP level were increased after six months. Both the intervention and control group also had a significant reduction in the waist circumference measurement after six months (p<0.05). The LMI-MA is clinically more effective than the standard LMI to improve the CMR profile of obese adults after six months.